The relationship between cortical grey to white matter signal contrast (GWC) and tau pathology in atypical AD. (December 2021) - Flaherty, Ryn; Krivensky, Samantha; Brickhouse, Michael; Carvalho, Nicole; Eckbo, Ryan; Salat, David H; Dickerson, Brad C.; Touroutoglou, Alexandra; Putcha, Deepti
Abstract: Background: Grey to white matter signal intensity ratio (GWC) has been studied as a novel metric of integrity and as a marker of neurodegeneration in Alzheimer's disease (AD). Regions with reduced GWC co‐localize with regions of cortical atrophy in AD (Salat et al. 2011; Salat et al. 2009). Cortical atrophy in AD robustly colocalizes with tau pathology measured using tau PET ligands (Putcha et al. 2019). For this study, we hypothesized that GWC co‐localizes with tau pathology and shows greater sensitivity to tau pathology than cortical atrophy across the atypical phenotypic spectrum of AD. Method: We studied 29 amyloid‐positive atypical AD patients, including 16 patients with posterior cortical atrophy (PCA), 10 with logopenic variant primary progressive aphasia (lvPPA), and 3 with an amnestic dysexecutive presentation. Whole‐cortex maps of GWC and cortical atrophy were generated for each individual using FreeSurfer. Tau PET ( 18 F‐Flortaucipir) signal was projected for each individual to the cortical surface using PETsurfer. Eta squared (η 2 ) was computed to determine the spatial overlap of each measure of neurodegeneration (GWC, cortical atrophy) with tau PET signal for each subject and then averaged across the whole group. Result: Both GWC and cortical atrophy revealed a pattern of neurodegeneration consistent with AD, including in medial parietal, lateral parietal, and posterior lateral temporal cortices. Lower GWC was also observed in several regions beyond the areas of cortical atrophy in patients including in bilateral dorsolateral and dorsomedial prefrontal cortices. Supporting our hypothesis, there was greater spatial overlap between the GWC and tau PET maps (η 2 = 0.30) compared to cortical atrophy and tau PET maps (η 2 = 0.24; t=4.49, p=0.0001). Conclusion: While both measures of neurodegeneration (GWC, cortical atrophy) showed a high degree of spatial overlap with tau PET signal across our sample of atypical AD participants, we conclude that GWC, a novel MRI‐derived biomarker of neurodegeneration in AD, correlates more strongly with AD‐related tau neuropathology than traditional cortical atrophy measures. This suggests that GWC could be a sensitive biomarker of AD‐related tissue changes that may represent neuronal injury or neurodegeneration. Further work is needed to establish how GWC tracks with tau pathology over time.